Constitutional and European scope of double taxation - López Espadafor, Carlos María (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
Double taxation is a vague concept, without an internal general legal definition and without useful parameters to limit it. The evolution undergone by the phenomenon of double taxation, both internationally and domestically, requires a review of the concept. The search for the legal parameters within which to consider this phenomenon legitimate or acceptable, demands the search for a conceptual concretion which is useful in this regard, in order to, from it, redefine the limits to the different ways for double taxation. The redefinition of double taxation should be done looking for a useful concretion of its limits and scope, which serves to determine when it is constitutional and when it is consistent with the principles of primary law of the European Union.
Keywords: double taxation; limit; constitutionality; European Union